Collaboration for new therapies: maximizing health and innovation - Mestre-Ferrandiz, Jorge; Meulien, Pierre; Ostwald, Dennis A.; Acha, Virginia (Frontiers in Public Health, 2024)
Introduction Innovative medicines and vaccines can provide direct health benefits to patients and populations by preventing, treating and curing diseases, and also drive wider socioeconomic and productivity gains. However, researching and developing them is complex and risky. Funding for life sciences R&D has different sources: public, charitable/NGO, and private sector. We believe there is consensus that all are required, although there is less understanding about their respective roles, synergies, and funding priorities. The purpose of this paper is to provide an overview of the current life sciences innovation ecosystem in Europe, highlighting challenges for funding and innovation of new therapies and our proposed options to address these. Methods The basis of this paper stems from the reflections made by the co-authors during a webinar with title “Collaboration for new therapies: maximising funding and innovation,” in March 2023, with further targeted literature reviews. Results We identify eight challenges in the European life sciences ecosystem, some closely related, and nine options that we think might be helpful to address them. Each option on its own can have different levels of ‘impact’, but collectively will provide synergies among them, and thus maximize their impact. Discussion It is critical to ascertain how the strengths of each actor can be leveraged to bring new medicines/treatments to market, quicker and more efficiently. We need a trusted environment, with strategic collaborations between the public and private sectors, and policy initiatives and incentives should be targeted to strengthen the infrastructure with the aim of fostering such optimal alliances.